A Farming System with Automatic Irrigation, Fertilization and Crop Protection - D., Gowthami; B., Rama Lakshmi Sravya; K., Poojitha; D., Yaswanth; CH., Hari Kumar (Journal of ISMAC, 2026)
This paper presents a smart agricultural system with the purpose of transforming agriculture through the integration of an automatic fertilization and irrigation system and a crop protection system. This system works with the recent IoT technology, Blynk App, sensor automation and smart pesticide spraying systems to increase agriculture productivity, save chemicals and water, and use available resources. Automatic crop protection system applies a microcontroller-based system for monitoring environmental parameters and providing selective pesticide sprinkling when needed to avoid wastage of chemicals and their impact on the environment. The automatic fertilization and irrigation systems constantly monitor soil moisture, temperature, pH and water level with sensors to ensure maximum growth of plants by providing precise irrigation and nutrient supply and combining this system as a cost-efficient solution for modern smart farming.